Effect of hyperventilation followed by a 1 min recovery on the Wingate performance - Kairouz, C.; Jacob, C.; El Hage, R.; Khoury, G.; Moussa, E.; Zouhal, H. (Science & Sports, 2013)
Introduction: The aim of this study was to measure the effect of a pre-exercise hyperventilation-induced respiratory alkalosis (HV) on performance determined during the Wingate test. Summary of facts: Eleven subjects performed the Wingate test twice: under normal conditions or after the completion of six maximal respiratory cycles (six maximal inspiration/expiration cycles done in 30 s) followed by a 1 min recovery period. The HV lead to a decrease of end-tidal carbon dioxide pressure (PETCO2) below 30 mmHg suggesting a significant increase of blood pH. Maximal power and mean power were not significantly different between the two tests. Conclusion: A brief hyperventilation followed by 1 min recovery does not affect performance determined during the Wingate test.